ADDIE-BASED CURRICULUM MODEL IN ISLAMIC EDUCATION: IMPACT ON LEARNING OUTCOMES - Elihami Elihami; Mohd. Azis; Mowafg Abrahem Masuwd; Dafit Afianto; Harley Agustian (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed the effectiveness of an ADDIE-based Islamic Education curriculum model in improving learning quality in five Madrasah Aliyah in South Sulawesi, Indonesia. A quantitative approach was employed using a quasi-experimental nonequivalent control group design. Participants included Islamic Education teachers and students selected through purposive sampling. Data were collected through achievement tests, student engagement questionnaires, and curriculum implementation assessment instruments. Analysis was conducted using descriptive statistics, independent sample t-tests, and N-gain scores to measure learning improvements.The results reveal that the experimental group significantly outperformed the control group, with higher post-test scores (M = 84.76) compared to pre-test scores (M = 63.42) and an N-gain of 0.58, while the control group showed lower improvement (M = 71.45; N-gain = 0.23). The difference was statistically significant (t = 8.41; p < 0.05), indicating the effectiveness of the ADDIE-based model in enhancing learning outcomes.The study extends instructional design theory by demonstrating that the ADDIE model can be effectively contextualized within Islamic Education without compromising value-based learning objectives. Practically, it supports teachers in improving instructional planning, implementation, and evaluation processes in madrasah contexts.